2014
DOI: 10.1080/00222348.2014.958422
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Micelle Formation of Nonionic Polyurethane in Water by Fluorescence Spectrophotometry

Abstract: A series of nonionic polyurethanes were dissolved in water and their miceller selfassembly behaviors were characterized by aid of a fluorescence spectrophotometer. Fluorescence and resonance light scattering techniques were carried out for characterizing the micelles, and information such as aggregation number, critical micelle concentration, micropolarity, and micelle volume change was obtained. The micropolarity decreased as the aggregation number increased. The nonionic polyurethane micelle volume with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The approximation of the corresponding aggregate concentrations yields similar weight portions between 6 and 11 wt % for both PUs. In general, the self-assembly of amphiphilic (nonionic) PUs into micellar structures is most-pronounced and thus commonly studied in aqueous environments 28,29 but also known in polar organic solvents. 30 In a former study, we correspondingly observed the complete aggregation of similar pEG-based PUs with terpyridine side groups in water while a mixture of aggregates and molecularly dissolved chains occurred in MeOH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The approximation of the corresponding aggregate concentrations yields similar weight portions between 6 and 11 wt % for both PUs. In general, the self-assembly of amphiphilic (nonionic) PUs into micellar structures is most-pronounced and thus commonly studied in aqueous environments 28,29 but also known in polar organic solvents. 30 In a former study, we correspondingly observed the complete aggregation of similar pEG-based PUs with terpyridine side groups in water while a mixture of aggregates and molecularly dissolved chains occurred in MeOH.…”
Section: ■ Results and Discussionmentioning
confidence: 99%